ANALISIS PENERAPAN PAJAK PENGHASILAN FINAL PASAL 4 AYAT 2 ATAS JASA KONTRUKSI (Studi Kasus Pada CV. Tuberta) - Meilinda Stefani Harefa; Andalkris Yuliasih Laia (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2022)
The purpose of this study was to analyze the application of the final income tax article 4 paragraph 2 on CV. Tuberta which includes calculation, deduction, deposit, and reporting. Based on the results of research for 2021 in the implementation of construction services the tax rate charged to CV. Tuberta 4%. In 2022 CV. Tuberta performs construction service activities as the executor and the tariff is 1.75%. The final income tax rate of article 4 paragraph 2 imposed both in 2021 and 2022 is in accordance with government regulations for the current year. Withholding and depositing taxes are carried out by the government treasurer as a service user. There are still tax reports that are reported late due to incomplete documents from service users. CV. Tuberta is expected to follow changes in tax regulations, especially those related to final income tax for construction services.